2021
DOI: 10.1017/s0033291721001604
|View full text |Cite
|
Sign up to set email alerts
|

Understanding outcomes in family-based treatment for adolescent anorexia nervosa: a network approach

Abstract: Background Family-based treatment (FBT) is the first-line treatment for adolescent anorexia nervosa (AN). Yet, remission is not achieved for about half of adolescents with AN receiving FBT. Understanding patient- and parent-level factors that predict FBT response may inform treatment development and improve outcomes. Methods Network analysis was used to identify the most central symptoms of AN in adolescents who completed the Eating Disorder Examination (EDE) prior to FBT (N = 409). Brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…Firstly, Levinson and coworkers in three different papers [ 57 59 ] used panel data to estimate interindividual networks (temporal, contemporaneous, and between-subject), as well as intra-individual networks (temporal and contemporaneous) for some of the patients in the sample. Other relevant studies aimed at assessing the treatment efficacy by applying statistical techniques [ 34 , 36 , 38 , 44 , 51 , 52 , 66 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, Levinson and coworkers in three different papers [ 57 59 ] used panel data to estimate interindividual networks (temporal, contemporaneous, and between-subject), as well as intra-individual networks (temporal and contemporaneous) for some of the patients in the sample. Other relevant studies aimed at assessing the treatment efficacy by applying statistical techniques [ 34 , 36 , 38 , 44 , 51 , 52 , 66 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they observed that centrality of symptoms at baseline was significantly associated with prognostic values for both recovery status and clinical impairment. Similarly, Hagan et al (2021) found that pretreatment central symptoms in adolescents with AN significantly predicted early response but did not predict remission. A third study (Olatunji et al, 2018) also found that the most central symptoms, namely interoceptive awareness and ineffectiveness , did not change after treatment.…”
Section: Resultsmentioning
confidence: 95%
“…assessment of treatment outcome (Calugi et al, 2021; Elliott et al, 2020; Hagan et al, 2021; Hilbert et al, 2020; Olatunji et al, 2018; Smith et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations